Strategi Guru Tahfidz dalam Membimbing Kegiatan Ekstrakurikuler Tahfidz Al-Qur’an untuk Meningkatkan Hafalan Siswa - Roisa Khoirotunnisa, Diva; Jasminto (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the strategies employed by tahfidz teachers in guiding the Qur’an memorization extracurricular program to enhance students’ memorization quality and character development at MAN 8 Parimono Jombang. The research identifies students’ memorization practices and analyzes how teachers design and implement mentoring strategies within a non-boarding school context. A qualitative approach with a case study design was applied to obtain an in-depth understanding of the learning process. Data were collected through observation, interviews, and documentation to provide a comprehensive picture of program implementation and its impact.The findings indicate that although no formal institutional policy specifically regulates the program, tahfidz teachers develop structured work plans and adopt adaptive learning strategies inspired by pesantren traditions. These strategies support systematic memorization while fostering positive character traits such as patience, consistency, and discipline. The extracurricular activity also contributes to students’ personal development by integrating cognitive and moral dimensions alongside academic achievement. Overall, the program demonstrates improved memorization outcomes and reflects an effective model for strengthening Qur’anic learning in non-boarding madrasah settings